Development and validation of a method for the analysis of five diamide insecticides in edible mushrooms using modified QuEChERS and HPLC-MS/MS. (15th December 2020) - Tian, Fajun; Qiao, Chengkui; Luo, Jing; Guo, Linlin; Pang, Tao; Pang, Rongli; Li, Jun; Wang, Caixia; Wang, Ruiping; Xie, Hanzhong
Graphical abstract: Highlights: This is the first study to determine five diamide insecticides in mushrooms. QuEChERS method was firstly used to extract diamide insecticides in mushrooms. The method showed satisfactory recovery and high sensitivity. Application of the method validation exhibited excellent results. Abstract: In this study, a new method for simultaneous determination of cyantraniliprole, chlorantraniliprole, tetrachlorantraniliprole, cyclaniliprole and flubendiamide in edible mushrooms by high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) combined with a modified QuEChERS procedure. The samples were extracted using acetonitrile and then cleaned up by primary secondary amine (PSA) and octadecylsilane (C18). The determination of these insecticides was achieved in less than 5 min using an electrospray ionization source in positive mode (ESI+) for cyantraniliprole and chlorantraniliprole, while negative mode (ESI−) for tetrachlorantraniliprole, cyclaniliprole and flubendiamide. The linearities of the calibrations for all target compounds were acceptable (R 2  ≥ 0.9922). The limits of detection and quantification were 0.05–2 μg kg −1 and 5 μg kg −1, respectively. Acceptable recoveries (73.5–110.2%) were acquired for these insecticides with RSDs less than 12.7%. The results demonstrated that the proposed method was effective and convenient for the determination of these insecticides in edible mushrooms.